PENGARUH PEMBELAJARAN INKUIRI TERBIMBING TERHADAP PEMAHAMAN KONSEP FISIKA PESERTA DIDIK - Muhammad Amran Shidik; Faradina Faradina; Pertiwi Pertiwi; Anas Irwan (Karst : JURNAL PENDIDIKAN FISIKA DAN TERAPANNYA, 2021)
This research was conducted with the aim of knowing whether there was an effect of guided inquiry learning on students' understanding of the concepts of physics. By using a quasi-experimental research method with. Non-Equivalent research design. Control Group Design in order to obtain two class groups, namely the experimental and control groups. Data were collected using an objective test of concept understanding in the form of a multiple-choice test with five choice options. The data obtained were then tested the prerequisites first. After the data is said to be distributed normally and homogeneously, it is followed by hypothesis testing using the t-test. The t-test result shows that the significance value is smaller than the α value (0.000 <0.05), so that Ho is rejected and Ha is accepted. Which means that there is an effect of understanding the concept of physics between participants being taught learning guided inquiry and being taught conventionally.